Scholar’s vocabulary-knowledge favored listening-reading tenets: Concurrences from Madura - Roziyan Adi Wicaksana; Shofiyatul Hasanah; Parahita Pradipta; Erfan Efendi (Institute of Advanced Engineering and Science, 2023)
The study objective was to seek the favored tenets betwixt mobile-assisted-language-learning (MALL) listening-reading appliances by video-conferencing-technology (VCT) and direct-listening-reading appliances to Madurese-scholar’s second-language (L2) vocabulary-knowledge (VK) listening-reading competencies. The analysis of variance (ANOVA), which produced concurrences, contained 41 scholars in two distinct emplacements amidst a Madurese-scholars preponderance and the different amounts in groups. Several significant conclusions emerged from the current ANOVA analysis. First, the comprehensive implication betwixt MALL listening-reading-appliance and direct-listening-reading-appliance to scholar’s L2-VK listening-reading competencies was not substantiated because it was more than level significant (0.440>0.05). Second, we convened cognizance by direct perception, inside and outside deliberation, and documented it. Third, the cross-examination eventualities of perception-documentation were coded, and research eventualities established the Madurese-scholar higher education framework to pervade case study evidence vacuity that aims to scrutinize: i) the Madurese-scholar teaching-learning peculiarities performance of MALL-VCT-Zoom and Smart-TV multimedia edification; ii) Madurese-scholar interminable concurrences in MALL-VCT-Zoom and Smart-TV; and iii) impediments obtain by MALL-VCT-Zoom and Smart-TV during participation in edification. Irrevocably, concurrence betwixt MALL-VCT-Zoom and smart-TV to scholars’ L2-VK listening-reading competencies were interrelated impacts as Madurese-scholars can learn conveniently with their necessity and concurrently utilize smart-TV or Zoom despite their impediments.